Factors Influencing Purchase Intention on MSME Product: Social Media Influencers, E-Wom, Online Trust, and the TAM Model Impact on Millenials and Gen Z in Jabodetabek - Alyanesia Fadhiya Brigin; Arif Imam Suroso; Ririn Wulandari (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The increasing development of the internet in this digital era brings many influences and benefits to people’s lives, especially for Millennials and Gen Z. These generations tend to use social media to share daily activities, including online shopping. Social media platforms like Instagram and TikTok have become frequently used for shopping.Purpose: The purpose of this study is to analyze the factors that influence purchase intention for MSME products, including an examination of the mediating role of online trust. Design/methodology/approach: This research employs a quantitative descriptive approach utilizing an online survey method. The study involves 148 respondents from Micro, Small, and Medium Enterprises (MSMEs) consumers using a purposive sampling technique through an online survey distributed via Google Forms. Data were analyzed using SEM-PLS, ensuring a thorough analysis of the factors influencing purchase intention. Finding/Result: The findings reveal the mediating role of online trust in mediating the effects of social media influencers and e-wom on consumer purchase intention. The results show that social media influencers, online trust, and perceived usefulness have a significant positive effect on purchase intention. Marketing MSME products requires identification from the consumer side, one of which is the socio-demographic characteristics formed by consumers when purchasing products on social media. The results of this study recommend MSMEs to promote through influencers, in addition to training for MSME actors on effective marketing strategies on social media, especially popular social media platforms such as Instagram and TikTok. Effective product marketing is essential to adapt to changes in the business environment and different consumer behaviors.Conclusion: The study underscores the importance of understanding consumer demographics for effective marketing on social media platforms like Instagram and TikTok. Also, leverage influencer marketing and provide targeted training to enhance their social media strategies, emphasizing the need for adaptive marketing approaches to meet changing consumer behaviors and business environments.Originality/value (state of art): This study contributes new insight into the consumer behavior of Millennials and Gen Z in Greater Jakarta, emphasizing the critical role of online trust in the digital shopping environment especially in social commerce.  Keywords:    purchase intention, MSME (micro, small, and medium enterprises), social media marketing, millennials and gen z, greater Jakarta (Jabodetabek)